Optimization ofWear Performance of Castor Oil based Lubricant using Taguchi Technique. (2017) - Suhane, Amit; Sarviya, R.M.; Siddiqui, A.R.; Khaira, H.K.
Abstract: Lubricants are used globally in wide range of applications varying from smaller to larger industrial machinery units under differentworking conditions. Lossof toxic lubricants in to the environment during usage owing to mishandling, accidental spillages, leaks, evaporation and other miscellaneous reasons hasresulted in rising environmental concerns. Escalating crude oil prices have further aggravated the problem to renew interest in development and usage of alternative resourceswhich are environmental friendly and acceptable.Owing to certain inherent technical properties and their ability towards biodegradability; vegetable oils possess potential as alternatives to reduce dependency on mineral oil for lubricant formulations. In present investigation, wear performance of castor oil based lubricant has been examined for low speed applications.The experimental testswere carried on the basis of Taguchi's L16orthogonal array considering the influence of prominent variable operating factors load, speed and blending ratio. Using Taguchi optimization method, optimum combination of these three factors have been reported.Wear performance of castor oil based lubricant in varying blending ratio viz; tribological poperties like coefficient of friction and wear scarhave been analyzed in four ball testing machine through experimental design prepared by Taguchi technique.